Nonlinear finite element analysis of failure modes and ultimate strength of flexible pipes. (July 2017) - Yoo, Dong-Hyun; Jang, Beom-Seon; Yim, Ki-Ho
Abstract: Designs of flexible pipe utilized in offshore dynamic riser applications need to be subjected to strength assessment over the entire length in relation to the dynamic motion of the connected floater. Such assessment includes many uncertain factors including soil properties, internal pressure, ocean metadata and others. Failure of flexible pipe, moreover, leads to serious financial loss and environmental degradation. Thus, flexible pipe failure modes and safety need to be evaluated in terms of ultimate strength under various loads. Ultimate strength assessment of flexible pipe is quite complicated and time-consuming compared with that of a steel catenary riser, due to the composite materials, geometric complexity and the contact mechanism between layers The material nonlinearity and large deformation, moreover, render stable convergence of nonlinear analysis to a solution problematic. This paper proposes practical and stable methods of ultimate-strength assessment using 8-layered and 5-layered 3D FE models subjected to axial tensile and compressive loads, respectively. In the 5-layered model, four inner layers (carcass, pressure sheath, pressure armour, and anti-friction tape) are replaced by one equivalent pressure layer which plays a role of withstanding pressure applied together with the axial compression. It aims to improve the convergence of nonlinear analysis by simplifying the interactions between layers. For each analysis, the failure mechanisms and the interactions between layers are investigated in detail with incremental loading. The effect of initial imperfection, i.e. ovalizations are also examined. In the compressive strength analysis, the influence of various external pressure are additionally studied. Highlights: The assessments of ultimate strength are quite complicated due to geometric complexity and contact mechanism between layers. This study proposes practical and stable methods for the ultimate strength assessment using 2D FE model and 3D FE model. From the ultimate strength analysis, the failure mechanisms and the interactions between layers are investigated. In case of compressive ultimate strength, the effect of external pressure on the ultimate strength is investigated.